Extraction optimization of bioactive compounds from ora-pro-nobis (Pereskia aculeata Miller) leaves and their in vitro antioxidant and antihemolytic activities. (1st November 2021) - Cruz, Thiago Mendanha; Santos, Jânio Sousa; do Carmo, Mariana Araújo Vieira; Hellström, Jarkko; Pihlava, Juha-Matti; Azevedo, Luciana; Granato, Daniel; Marques, Mariza Boscacci
Highlights: The extracts of ora-pro-nobis (OPN) leaves present antioxidant activity. This is the first report of caffeoyl and coumaroyl hexaric acids in OPN leaves. The optimized extract (OP) was obtained with 60% water, 40% ethanol and 0% acetone. OP inhibits lipid peroxidation and hypotonic and H2 O2 -induced hemolysis. OP presents no cytotoxicity against cancer and normal cells. Abstract: Ora-pro-nobis ( Pereskia aculeata Miller) is a non-conventional food plant common in Brazil. The objective of this study was to optimize the extraction of bioactive phenolic compounds from ora-pro-nobis leaves by employing solvent mixtures. Ten extracts were obtained with water, ethanol, acetone, and their binary and ternary mixtures, evaluating the chemical composition, antioxidant activity and bioactivities in vitro . The response surface methodology was applied to model the results and calculate the optimal solvent composition, which is 60% water, 40% ethanol and 0% acetone. The optimized extract is rich in phenolic compounds (64 mg GAE/g) and proteins (823 mg/g) and presents antioxidant activity (in intracellular media as well) and inhibits lipid peroxidation (32%) along with hypotonic hemolysis (H50 = 0.339%), it does not present toxicity in vitro against cancer and normal cells. This is the first report of chicoric, caffeoyl-hexaric and coumaroyl-hexaric acids and some glycosylate derivatives of flavonols in ora-pro-nobis leaves.